2017
DOI: 10.1007/s00394-017-1465-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of urinary iodine levels in women of childbearing age during and after pregnancy

Abstract: In an iodine sufficient area for the general population, iodine excretion was lower during than after pregnancy when factors affecting iodine intake were controlled for. Current recommendations of median UIC during pregnancy are based on the equivalence between iodine intake and UIC estimated from studies in non-pregnant populations, which might lead to overestimation of iodine deficiency during gestation. Further studies should evaluate the equivalence between iodine intake and its urinary excretion during pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…A Spanish study reported that the median UIC of lactating women was 142 µg/L from [19]. The median UIC of 380 lactating women in Shanghai in 2012, China, was 131.1 µg/L and 36.8% of the participants and had iodine de ciency of < 100 µg/L with a cross-sectional survey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Spanish study reported that the median UIC of lactating women was 142 µg/L from [19]. The median UIC of 380 lactating women in Shanghai in 2012, China, was 131.1 µg/L and 36.8% of the participants and had iodine de ciency of < 100 µg/L with a cross-sectional survey.…”
Section: Discussionmentioning
confidence: 99%
“…According to the 24-hour meal review and dietary record evaluation, the current nutritional iodine intake of lactating women in Shanghai is insu cient. In 2017, a Spanish study found that the median nutritional iodine intake of lactating women was 125 µg/day (IQR 104, 154) [19]. Chinese residents' iodized salt consumption rate has continued to decline, and the iodized salt coverage rate in Shanghai has decreased to 16.91% from 2010 to 2015 [10].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study compared UIC in women during and after pregnancy and found that in an iodine sufficient area, iodine excretion was lower during than after pregnancy. However, the current standard during pregnancy recommended by WHO/ UNICEF/ICCIDD is based on non-pregnant populations: this might lead to overestimation of iodine deficiency during gestation, so the lower limit may be too high (24) . Monitoring by the Shanghai CDC showed that the median UIC in children aged 8-10 years was >100 μg/l after the implementation of the USI policy, indicating that children aged 8-10 years have sufficient iodine intake (12) .…”
Section: Discussionmentioning
confidence: 99%
“…Also, despite some countries being iodine sufficient in the general population, many pregnant women in those countries are still iodine deficient. 7 , 97 A subset of the INMA study showed that iodine intake during pregnancy was significantly higher than 4 years after birth, 73 which was related to a decrease in dairy-product intake after pregnancy 73 and suggests that intakes from adult studies are not a good proxy for iodine intake during pregnancy.…”
Section: Discussionmentioning
confidence: 99%